The German excellence initiative and efficiency change among universities, 2001-2011 - Bastian Gawellek; Marco Sunder (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2016)
The "Excellence Initiative" is a prestigious third-party funding program for German universities, organized as a research contest. We investigate whether universities in this program (or that prepared an application) had different trends in terms of productivity and technical efficiency than universities that did not apply for the program, albeit these dimensions were not the target of the program. While universities became more efficient if the extra funding through the program is included, we do not find a substantially positive effect that extends beyond this funding. The evidence even suggests that applicants suffered a drop in efficiency at the time of applying. All this does not rule out, however, that research-oriented universities jointly gained productivity through increased competition between them.
Keywords: I23; 330; Efficiency; Malmquist index; German Research Foundation; DFG